Information architecture for the implementation of a technological platform that manages research production in higher education institutions (2019)
Scientific communication and diffusion is one of the challenges of higher education institutions, related to the implementation of strategies of free access to the scientific and technological productivity of the teachers and researchers of the institutions, which allow to increase the visibility and impact of the research, for which a model of information architecture of the technological platform for the management of the investigative production of teachers and researchers was designed, under an environment focused on satisfying the information needs of the users that allows to organize, to group and to visualize the information by means of metadata. The research is of exploratory-descriptive type, through which the products of science, technology and innovation that should be visible in the technological platform were identified, generating as a result an architecture model-view-controller, with data storage in a relational database, which has access through a RESTful API made in Java, the views and controllers were made in HyperText markup language and JavaServer pages respectively. MySQL was used as a relational database engine to store information and MYSQL Workbench as a platform for the construction of the relationship model between entities, tables and columns; which will be used as a framework for the design, planning and implementation of the technological platform.